Displacement of Methane by Coadsorbed Carbon Dioxide Is Facilitated In Narrow Carbon Nanopores - Kowalczyk, Piotr; Gauden, P.; Terzyk, A.; Furmaniak, S.; Harris, P. (American Chemical Society, 2012)
By using simulation methods, we studied the adsorption of binary CO2-CH4 mixtures on various CH4 preadsorbed carbonaceous materials (e.g., triply periodic carbon minimal surfaces, slit-shaped carbon micropores, and Harris’s virtual porous carbons) at 293 K. Regardless of the different micropore geometry, two-stage mechanism of CH4 displacement from carbon nanospaces by coadsorbed CO2 has been proposed. In the first stage, the coadsorbed CO2 molecules induced the enhancement of CH4 adsorbed amount. In the second stage, the stronger affinity of CO2 to flat/ curved graphitic surfaces as well as CO2-CO2 interactions cause the displacement of CH4 molecules from carbonaceous materials. The operating conditions of CO2-induced cleaning of the adsorbed phase from CH4 mixture component strongly depend on the size of the carbon micropores, but, in general, the enhanced adsorption field in narrow carbon ultramicropores facilitates the nonreactive displacement of CH4 by coadsorbed CO2. This is because in narrow carbon ultramicropores the equilibrium CO2/CH4 selectivity (i.e., preferential adsorption toward CO2) increased significantly. The adsorption field in wider micropores (i.e., the overall surface energy) for both CO2 and CH4 is very similar, which decreases the preferential CO2 adsorption. This suppresses the displacement of CH4 by coadsorbed CO2 and assists further adsorption of CH4 from the bulk mixture (i.e., CO2/CH4 mixing in adsorbed phase).